The effect of the Violence Prevention through Urban Upgrading (VPUU) intervention on violence-related injuries presenting to health facilities in Khayelitsha and Nyanga - Trupe, Lydia (Institute of Infectious Disease and Molecular Medicine, 2017)
Background: Violence is one of the leading causes of morbidity and mortality in South Africa's Western Cape province. Recent efforts, both globally and locally, have focused on using emergency room surveillance systems to collect data on violent injuries and to use these data to inform comprehensive, sustainable interventions such as urban upgrading. Drawing on insights from criminology, these urban upgrading interventions have sought to use environmental design to ameliorate socio-ecological factors related to violence. Objective: To use injury surveillance data in order to describe the pattern of violent injuries presenting to health facilities in the communities of Khayelitsha and Nyanga and to assess the effect of the Violence Prevention through Urban Upgrading programme (VPUU) on risk of violent non-fatal injury in these two areas. Methods: We conducted a case-control study using data from a series of semi-annual rapid assessments to compare violent and non-violent injuries in adults presenting to five heath facilities in Khayelitsha and Nyanga between September 2013 and October 2015. Multivariable logistic regression was used to assess the risk of violent injury with respect to demographic and behavioural characteristics and exposure to the VPUU intervention. Results: Multivariable analysis of 1,753 complete cases revealed that living in a VPUU intervention area was protective against presentation for violent injury when controlling for other risk factors (OR=0.75, p=0.022). Age, gender, race, and alcohol consumption were also found to be significantly associated with presentation for violent injury. There was a statistically significant interaction effect between alcohol and gender; the association between alcohol consumption and violent injury was stronger in women than in men. Conclusion: This study highlights the demographic and behavioural factors associated with violent injury and provides preliminary evidence of the reduction of violent injury risk in VPUU intervention areas.